Improving Environmental Sensitivity through Problem-Based Hybrid Learning (PBHL): An Experimental Study - Amin, S.; Sumarmi, S.; Bachri, S.; Susilo, S.; Mkumbachi, R. L.; Ghozi, A. (Jurnal Pendidikan IPA Indonesia, 2022)
Students need to possess sensitivity to the environment in order to behave positively when they notice a problem and find the right solution. This study intends to investigate whether the PBHL model affects the environmental sensitivity of Social Science Education students on environmental issues and conservation materials. The quasi-experimental design of the pretest-posttest controlled group was used in this study. Students of the Social Science Education Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia, were selected as research subjects using a purposive sampling technique. The research subjects were determined to consist of class D as the experimental class (29 students) and class B as the control class (29 students). Questionnaires with a Likert scale of 1 (strongly disagree) – 4 (strongly agree) were used in taking student environmental sensitivity data on environmental issues and conservation materials, totaling 28 items with indicators: knowledge, attitudes, and skills. Subsequently, the data were tested for normality and homogeneity and analyzed using an independent sample t-test. The results showed that the PBHL model had a significant effect on the environmental sensitivity of Social Science Education students on environmental issues and conservation materials ((p (0.009) α (0.05)). The average results of the sensitivity of the experimental class environment (N-Gain = 13.29) were higher than the control class (N-Gain = 8.75). This goal can be achieved through the syntax in the PBHL model. The suggestion for further research is that it is necessary to develop further by combining the PBHL model and interactive mobile learning media as a means for students to investigate and actualize problem-solving.